2015
DOI: 10.15380/2277-5706.jcsr.14.059
|View full text |Cite
|
Sign up to set email alerts
|

Role of dyslipidaemia and lipid peroxidation in pregnancy induced hypertension

Abstract: Background: Pregnancy induced hypertension (PIH) contributes greatly to maternal morbidity and mortality. Altered lipid profile and increased lipid peroxidation activate endothelial dysfunction and atherothrombosis leading to PIH. Therefore, estimation of lipid profile with serum malondialdehyde (MDA) in pregnancy may be helpful in predicting the development of PIH and further progression. Material and methods:In this prospective case-control study, serum lipid profile and MDA were estimated in 70 PIH subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…A study conducted by Gandhi M et al, 14 There was a positive correlation between serum uric acid with systolic (r = +0.454, P <0.001) and diastolic blood pressure (r = +0.471, p < 0.001). Similar findings were seen in studies done by Sonagra et al, 19 P Josephine et al 20 and Saxena et al 21 Mustaphi et al 22 observed that when the levels of diastolic BP is increased, the levels of serum uric acid was also increased, concluding a positive correlation between diastolic BP and serum uric acid. Correlation Coefficient r value with systolic BP in similar studies by Sonagra et al, 19 P Josephine et al 20 and Saxena et al 21 were 0.408, 0.287 and 0.214 respectively whereas r value with diastolic BP in same studies were 0.420, 0.235 and 0.367 respectively.…”
Section: Discussionsupporting
confidence: 84%
“…A study conducted by Gandhi M et al, 14 There was a positive correlation between serum uric acid with systolic (r = +0.454, P <0.001) and diastolic blood pressure (r = +0.471, p < 0.001). Similar findings were seen in studies done by Sonagra et al, 19 P Josephine et al 20 and Saxena et al 21 Mustaphi et al 22 observed that when the levels of diastolic BP is increased, the levels of serum uric acid was also increased, concluding a positive correlation between diastolic BP and serum uric acid. Correlation Coefficient r value with systolic BP in similar studies by Sonagra et al, 19 P Josephine et al 20 and Saxena et al 21 were 0.408, 0.287 and 0.214 respectively whereas r value with diastolic BP in same studies were 0.420, 0.235 and 0.367 respectively.…”
Section: Discussionsupporting
confidence: 84%
“…Many studies determined contradictory results of elevated ROS and TBARS but reduced antioxidants in PE (Cohen et al, 2015;Mutlu-Türko et al, 1998). Increased TBARS levels showed the increase lipid peroxidation in cells and may suggest decreased enzymatic free radical scavenging capacity in preeclamptic patients (Biri et al, 2007;Gupta et al, 2009;Saxena et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Jin WY et al, Saha D et al, Saxena S et al, Vidyabati RK, Islam NAF and Aziz R they all agree on the fact that dyslipidemia was significantly associated with pre eclampdia and eclampsia. [6][7][8][9][10][11] As hypertensive disorder developed, there was development of fetal complications. The women with severe dyslipidemia developed fetal complication of severe IUGR and IUD in their late second and early third trimester with very poor outcome.…”
Section: Discussionmentioning
confidence: 95%